2022
DOI: 10.1001/jamaoto.2021.4430
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of an Early Childhood Hearing Screening Program in a Low-Income Setting

Abstract: ImportanceEarly identification of childhood hearing loss through newborn hearing screening mitigates permanent speech, language, and developmental delays, but many children are lost to follow-up or develop postnatal hearing loss. Early childhood hearing screening programs may help identify these children, but evidence on their outcomes is limited.ObjectiveTo assess outcomes from a low-income, preschool-based hearing screening program and risk factors for hearing loss in this population.Design, Setting, and Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(51 reference statements)
1
10
0
1
Order By: Relevance
“…We found that hearing thresholds differed by sex except for the hearing thresholds of the left ear at 1,000 Hz, with higher thresholds for girls than for boys, but no sex difference in screening failure rates, which is consistent with the findings of a study on preschool children ( 39 ). This result may indicate that girls have a higher risk of hearing deterioration than boys even if they can pass the hearing screening.…”
Section: Discussionsupporting
confidence: 90%
“…We found that hearing thresholds differed by sex except for the hearing thresholds of the left ear at 1,000 Hz, with higher thresholds for girls than for boys, but no sex difference in screening failure rates, which is consistent with the findings of a study on preschool children ( 39 ). This result may indicate that girls have a higher risk of hearing deterioration than boys even if they can pass the hearing screening.…”
Section: Discussionsupporting
confidence: 90%
“…To the Editor We read with great interest the article by Brodie et al, titled “Outcomes of an Early Childhood Hearing Screening Program in a Low-Income Setting.” Of primary importance, this retrospective, community-based cohort study demonstrated that preschool screening programs were a useful method for children aged 2 to 6 years from urban, low-income public preschools. Furthermore, the authors should be singularly commended for attaching importance to the value of teacher concern for hearing loss, language, or speech development.…”
mentioning
confidence: 75%
“…39,40 Furthermore, it should be noted that there are several influencing factors that affect the observation of the tympanic membrane and thus the accuracy in diagnosis during otoscopic examination, such as in the conditions when the external ear canal is partly or completely blocked by cerumen, or when children are unable or unwilling to cooperate with the examination. [41][42][43][44] Therefore, it is crucial to obtain high-quality otoscopic images as input data to ensure a reliable and accurate DL model for predicting CHL in ears with OME.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the diagnostic accuracy for detecting OME using otoscopy is between 60% and 70%, whereas the sensitivity and specificity of tympanometry can reach to 70% to 90% for the detection of OME, but it is dependent on patient cooperation . Furthermore, it should be noted that there are several influencing factors that affect the observation of the tympanic membrane and thus the accuracy in diagnosis during otoscopic examination, such as in the conditions when the external ear canal is partly or completely blocked by cerumen, or when children are unable or unwilling to cooperate with the examination . Therefore, it is crucial to obtain high-quality otoscopic images as input data to ensure a reliable and accurate DL model for predicting CHL in ears with OME.…”
Section: Discussionmentioning
confidence: 99%